Adaptasi Kebijakan Standar Pendidik bagi Pengajar Kitab Kuning dalam Manajemen Pondok Pesantren Darussalim Bati-Bati Kabupaten Tanah Laut - Nur Sobah; Muhammad Agussalim; Nuryadin Nuryadin (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study examines the adaptation of educator standards policies for kitab kuning teachers at Darussalim Bati-Bati Islamic Boarding School, Tanah Laut Regency. Using a qualitative case study approach, data were collected through interviews, observations, and documentation involving five key informants. The findings indicate that the pesantren adapts educator standards by integrating formal academic qualifications with Salafiyah scholarly competencies. This adaptation is reflected in the gradual upgrading of educators’ academic qualifications to the bachelor’s degree (S1) level while maintaining scholarly competence, moral character, and pesantren experience as essential requirements. Recruitment, evaluation, and professional development are implemented through competency-based management, continuous training, and supervision. Major challenges include educator shortages, administrative demands, and efforts to preserve Salafiyah identity amid educational standardization. The study concludes that national education standards and the Salafiyah scholarly tradition can be integrated within an adaptive and sustainable pesantren management system.